A Post State-Centric Analysis of China-Africa Relations Internationalisation of Chinese Capital and State-Society Relations in Ethiopia - Ziso, Edson (Critical Studies of the Asia-Pacific,, 2018)
This book offers a new alternative to understanding the relationship between China and Africa. Here, the author not only explores the changing nature of Ethiopia's internal politics as a result of Chinese investment and commercial links, but also compellingly questions the existing state-centric macro or strategic investigation of China-Africa relations. By thoroughly reviewing and deploying the 'second image reversed' approach and the relational concept of state power analytical approaches, Ziso challenges the Western-centric Weberian conceptualization of state. This volume presents an eclectic approach to interpret the state transformation in Ethiopia in light of Chinese capital, arguing for a "state in society" framework which does not treat the state as a unitary black box. This analysis challenges the conventional binary staple which is often framed on whether China is the new imperialist power plundering Africa's resources or is Africa's historically all-weather friend. This volume offers an original contribution to knowledge on China's relations with Ethiopia in particular, and with Africa in general. Edson Ziso is a Visiting Research Fellow in the Department of Politics and International Studies at the University of Adelaide, South Australia.